HUBUNGAN KONSUMSI IKAN DENGAN TINGKAT KECUKUPAN PROTEIN ANAK BALITA PADA KELUARGA NELAYAN DI KELURAHAN PASIR BIDANG KECAMATAN SARUDIKKABUPATEN TAPANULI TENGAH - Christina Simanjuntak; Albiner Siagian; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Fish is the main source of protein for fisherman families. Kelurahan Pasir Bidang is one of the areas that majority the regions have livelihood as fisherman, either catching fisherman or working fisherman. Therefore, almost in every day they consume fish as side dishes including their toddler. The purpose of this research is to understand the relation of fish consumption and protein sufficiency rate of the toddler in the fisherman families in Kelurahan Pasir Bidang, Kecamatan Sarudik, Kabupaten Tapanuli Tengah. This research was observational with cross-sectional design. The population of toddlers are 281 toddlers, and the samples are 74 toddlers. Sampling technique was done by simple random sampling technique. Data which taken from the research are the quantity of fish consumption and the daily protein sufficiency. Data were collected with use the 2x24 hours food recall and food frequency method. The relation of fish consumption and protein sufficiency rate was taken by chi-square test with p<0,005. The result of the research showed the type of fish that frequently consumed is layang fish (sea food) about 97,5% and infrequently consumed is lele fish about 24,3%. Average of toddlers fish consumption is 97,5 grams with average of daily protein sufficiency is 21,45 grams. The result of the research also showed that there is the relation between the total of fish (gr) with the protein sufficiency rate of toddlers among aged 12-36 months (p=0,003) and also among aged 37-60 months (p=0,004). Based on the results of the research, it is suggested that the mothers who are responsible to prepare food in the household can more increase the fish protein consumption with use the source of fish protein that got from the fishermen, and to improve public knowledge about nutrition, especially about the consumption of fish and the contribution of the protein needs, is expected to the local health officer to give conseling to a lot of people. Keywords : toddler, fish consumption, protein sufficiency rate